Barriers and Facilitators to Implementation of Antibiotic Stewardship Programmes in Hospitals in Developed Countries: Insights From Transnational Studies - Rzewuska, Magdalena; Duncan, Eilidh M.; Francis, Jill J.; Morris, Andrew M.; Suh, Kathryn N.; Davey, Peter G.; Grimshaw, Jeremy M.; Ramsay, Craig R. (Frontiers in Sociology, 2020)
Objectives: To identify perceived influences on implementation of antibiotic stewardship programmes (ASPs) in hospitals, across healthcare systems, and to exemplify the use of a behavioral framework to conceptualize those influences. Methods: EMBASE and MEDLINE databases were searched from 01/2001 to 07/2017 and reference lists were screened for transnational studies that reported barriers and/or facilitators to implementing actual or hypothetical ASPs or ASP-supporting strategies. Extracted data were synthesized using content analysis with the Theoretical Domains Framework as an organizing framework. Commonly reported influences were quantified. Results: From 3,196 abstracts 75 full-text articles were screened for inclusion. Eight studies met the eligibility criteria. The number of countries involved in each study ranged from 2 to 36. These studies included a total of 1849 participants. North America, Europe and Australasia had the strongest representation. Participants were members of special interest groups, designated hospital representatives or clinical experts. Ten of the 14 theoretical domains in the framework were present in the results reported in the included studies. The most commonly reported (≥4 out of 8 studies) influences on ASP implementation were coded in the domain “environmental context and resources” (e.g., problems with data and information systems; lack of key personnel; inadequate financial resources) and “goals” (other higher priorities). Conclusions: Despite an extensive transnational research effort, there is evidence from international studies of substantial barriers to implementing ASPs in hospitals, even in developed countries. Large-scale efforts to implement hospital antibiotic stewardship in those countries will need to overcome issues around inadequacy of information systems, unavailability of key personnel and funding, and the competition from other priority initiatives. We have enhanced the evidence base to inform guidance by taking a behavioral approach to identify influences on ASP uptake. Systematic review registration: PROSPERO registration number CRD42017076425.